Peningkatan hasil belajar senam lantai guling ke depan dengan menggunakan media matras dan variasi pembelajaran pada siswa kelas X.1 - Agus Sukaryono (JPPTK: Jurnal Pendidikan Pembelajaran & Penelitian Tindakan, 2021)
Floor gymnastic roll-formward is one of the subject matter in Sports and Health Education which includes in KTSP. Therefore, floor gymnastics roll-forward is taught in every school. Based on the earlay observations in SMAN Kunir Lumajang on the teaching of Sports and Health Education on floorgymnastics subject matter at X.1 class, it appears that students are still difficult to study the movement of the floor gymnastics given by the teacher. Among difficulties experienced by students use the neck and not the head. The process is as they are having impact with the mat. Most of the students use the neck and not the head. The method used in this research is a class action research through three cycles. The subjects were researcher himself as a Sports and Health Education teacher and the students of X.I grade at SMAN Kunir Lumajang. The number of students in the class is 35 students. The conclusion that can be drawn through this study is a mattress medium and learning variety provided by the teacher can enhance the learning process and outcomes on floor gymnastics roll-forward at the students of X.1 grade of SMAN Kunir Lumajang.